Mirizzi syndrome masquerading as gallbladder carcinoma: a case report on diagnostic challenges and multidisciplinary management - Yang, Yu; Hou, Yiwei; Yi, Li; Zhou, Hang; Tang, Lihua; Fu, Yunxi; Hu, Mingzheng; Xing, Rongchun (Frontiers in Medicine, 2025)
BackgroundMirizzi syndrome is a rare condition that is frequently misdiagnosed as gallbladder cancer due to overlapping clinical and imaging features. This case underscores the diagnostic challenge of differentiating these two conditions and offers insights into managing such complex presentations.Case summaryA 45-year-old female presented with obstructive jaundice and elevated liver enzymes. Imaging studies, including CT, PET-CT, and MRCP, revealed gallbladder wall thickening, bile duct obstruction, and a high suspicion of malignancy. Tumor markers were within normal limits. Intraoperatively, extensive adhesions, gallbladder wall oedema, and bile duct compression consistent with Mirizzi syndrome were identified. A partial cholecystectomy and bile duct exploration with stent placement were performed. Histopathological examination confirmed chronic cholecystitis with inflammation, but no evidence of malignancy. The patient had an uneventful recovery, with complete resolution of her symptoms.ConclusionMirizzi syndrome can closely resemble gallbladder cancer, making careful surgical exploration and pathological evaluation essential for accurate diagnosis.